PHYSICAL WORK ENVIRONMENT AND ACADEMIC STAFF PRODUCTIVITY IN UNIVERSITIES IN ENUGU STATE, NIGERIA - Chika. C., Uchendu; Emeka Samue, Nnaji,; Innocent Arinze, Nwafor, (IJRDO - Journal of Social Science and Humanities Research, 2016)
This study was designed to ascertain the relationship between physical work environment and academic staff productivity in universities in Enugu state. Two research questions and two hypotheses were formulated to guide the study and survey design was adopted for the study. Stratified random sampling technique was adopted to select 400 out of 2002 academic staff of the various faculties, institutions and centres in University of Nigeria Nsukka and Enugu State University of Science and Technology. A researcher’s designed instrument on a fourpoint rating scale titled “physical work environment and academic staff productivity questionnaire” (PWEASPQ) was adopted to elicit responses from the respondents and to collect data. Data analysis was done using person product moment correlation analysis (P) at 0.5 level of significant. The results showed a significant relationship between physical work environment in terms of library facilities and classroom space and academic staff productivity. Based on this result, it was recommended that Government, private bodies and other stakeholders in education should provide more funds to universities through allocations and donations in order to help universities meet their needs in the provision of physical facilities.